Testing for pharmacogenomic predictors of ppRNFL thinning in individuals exposed to vigabatrin - Boothman, Isabelle; Clayton, Lisa M.; McCormack, Mark; Driscoll, Alexandra McKibben; Stevelink, Remi; Moloney, Patrick; Krause, Roland; Kunz, Wolfram S.; Diehl, Sarah; O’Brien, Terence J.; Sills, Graeme J.; de Haan, Gerrit-Jan; et al. (Frontiers in Neuroscience, 2023)
Background: The anti-seizure medication vigabatrin (VGB) is effective for controlling seizures, especially infantile spasms. However, use is limited by VGB-associated visual field loss (VAVFL). The mechanisms by which VGB causes VAVFL remains unknown. Average peripapillary retinal nerve fibre layer (ppRNFL) thickness correlates with the degree of visual field loss (measured by mean radial degrees). Duration of VGB exposure, maximum daily VGB dose, and male sex are associated with ppRNFL thinning. Here we test the hypothesis that common genetic variation is a predictor of ppRNFL thinning in VGB exposed individuals. Identifying pharmacogenomic predictors of ppRNFL thinning in VGB exposed individuals could potentially enable safe prescribing of VGB and broader use of a highly effective drug. Methods: Optical coherence topography (OCT) and GWAS data were processed from VGB-exposed individuals (n=71) recruited through the EpiPGX Consortium. We conducted quantitative GWAS analyses for the following OCT measurements: 1) average ppRNFL, 2) inferior quadrant, 3) nasal quadrant, 4) superior quadrant, 5) temporal quadrant, 6) inferior nasal sector, 7) nasal inferior sector, 8) superior nasal sector, and 9) nasal superior sector. Using the summary statistics from the GWAS analyses we conducted gene-based testing using VEGAS2. We conducted nine different PRS analyses using the OCT measurements. To determine if VGB-exposed individuals were predisposed to having a thinner RNFL, we calculated their polygenic burden for retinal thickness. PRS alleles for retinal thickness were calculated using published summary statistics from a large-scale GWAS of inner retinal morphology using the OCT images of UK Biobank participants. Results: The GWAS analyses did not identify a significant association after correction for multiple testing. Similarly, the gene-based and PRS analyses did not reveal a significant association that survived multiple testing. Conclusion: We set out to identify common genetic predictors for VGB induced ppRNFL thinning. Results suggest that large-effect common genetic predictors are unlikely to exist for ppRNFL thinning (as a marker of VAVFL). Sample size was a limitation of this study. However, further recruitment is a challenge as VGB is rarely used today because of this adverse reaction. Rare variants may be predictors of this adverse drug reaction and were not studied here.